Public Service Innovation as a Strategy for Increasing Regional Innovation in Probolinggo City - Arwanto Harimas Ginting; Adi Suhendra (International Journal of Regional Innovation, 2022)
This research is about innovation in the field of public services carried out by the City of Probolinggo.This research is important and relevant to be discussed because itThis innovation can solve problems from the aspect of limited funds for sanitation and technology development which are considered complicated andthe introduction of the SIBER-PAM strategy that can guarantee an increase in the quality of services for the community. Thus, the two innovations gave rise to various strategies that offer convenience in the use of public services.And can be an inspiration for other regions in order to overcome the same problem. The population in this study is in areas that have implemented policies orinnovation in the field of public services. While the sample in this study isinnovations carried out by the Probolinggo City government are called Si Inol Aja innovations (Innovation System for Arisan Services / Latrine Installments) and innovationsEasier Access Based on "SIBER-PAM" (Socialization of Information Based on People's Education - Drinking Water Company). The results of this study indicate thatSi Inol Aja has proven to be one of the most effective ways to eradicate open defecation (BABs), namely people have healthy latrines with technological convenience, namely a direct cast system on the spot, having healthy latrines is not difficult and inexpensive, people have a latrine faster healthy without having to wait for help from the government, strengthen participation and community self-reliance, provide new skills for craftsmen who can expand their job opportunities in the surrounding area, and grow a synergistic partnership between the government, the community and the business world to realize better sanitation.Meanwhile, the introduction of the SIBER-PAM strategy can guarantee an increase in the quality of services for the community. The presence of SIBER-PAM can provide education to the public, especially customers of PDAM Kota Probolinggo and the means of socializing the services provided at this time have innovated to become more modern. Thus, through this strategy, conveniences in the use of public services will be offered.